Starch modification by ozone: Correlating molecular structure and gel properties in different starch sources - Castanha, Nanci (2020)
ABSTRACT Cassava, corn and potato starches were subjected to ozone processing under the same conditions, in order to allow comparisons. The molecular structure was evaluated using two chromatographic analyses: high-performance size-exclusion chromatography (HPSEC) coupled to multiangle laser light scattering (MALLS) and differential refractive index (RI) detectors, and gel permeation chromatography (GPC). Both proved the molecular depolymerization caused by ozonation, as well as illustrated the different behavior of each starch source – in special in relation to their molar mass dispersity. The granular morphology was not affected by ozone processing. On the other hand, the starch properties were affected by ozonation. In general, the apparent viscosity decreased during pasting, as well as the complex modulus (G*) of the immediately formed gels. After cooling and storage, however, the gels' strength increased or decreased due to ozonation, depending on the starch concentration. In general, results for cassava and potato starches were similar, while corn starch presented an opposite behavior. The results illustrated the relationship among ozonation conditions, starch source and analysis conditions, as well as their influence on the samples’ behavior and functional properties.